Komparasi Kinerja Perbankan Syariah Di ASIA Dengan Pendekatan Maqasid Syariah - Rilanda Adzhani; Rini Rini (Jurnal Akuntansi dan Keuangan Islam, 2017)
The purpose of this research was to analyze whether there are differences the performance of Islamic banking in Asia, based on the concept of Maqasid al-Shari’ah, using MI (Maqasid Index) value. This research was using data from financial report and annual report which were provided by each Islamic bank sample. This research was using 3 samples of Islamic banks for each country (Indonesia, Malaysia, Iran, Saudi Arabia, United Arab Emirates, Kuwait, and Qatar), so the total sample of Islamic banks were 21 Islamic banks. The total observation were 63 during three years period (2013-2015). The Kolmogorov-Smirnov tests were used to test the normality of data and the hypothesis testing was using Analysis of Variance (ANOVA). The result of this research showed that MI value, second sharia objectives called establishing justice, and third sharia objectives called public interest in Islamic banking in Indonesia showed no significant difference with Islamic banking in Malaysia, Iran, Saudi Arabia, United Arab Emirates, Kuwait, and Qatar